"Internet +" for Targeted Poverty Alleviation by Listed Companies - A Case Study of Alibaba Group - Liu, Yong; BI, Chuanchen (Technium Social Sciences Journal, 2022)
Based on the "Internet +" concept in 2012 and the "Targeted Poverty Alleviation" strategy in 2013, many companies have found new ways to alleviate poverty through the "Internet +", which has injected new vitality into impoverished area, and also helped enterprises to promote their development in the course of poverty alleviation. This paper aims to promote the development of enterprises in the process of poverty alleviation through literature analysis and case studies. This paper intends to help more companies understand the role of "Internet +" in poverty alleviation through literature analysis and case studies, as well as how to consolidate the results of poverty alleviation and prevent the return of poverty with effective poverty alleviation methods, so as to achieve the simultaneous development of poverty alleviation and company business.